Comercialización de calzados en el Cantón Alfredo Baquerizo Moreno (JUJAN) - Bravo Mota, Edinson Andrés (2020)
Fashion is an aspect that has always conditioned the behavior of people and society in general, since it generates needs beyond the basic for people. Footwear is a basic element for people, but it is also obtained through innovative processes that develop trends. Within the Alfredo Baquerizo Moreno canton, there is no business that exclusively offers footwear and it is here that the business opportunity arises to design a technical proposal for entrepreneurship, based on a business model of a shoe store exclusively for men. The result of the technical feasibility processes provided positive results for the future implementation of this business. This business idea was validated by the CANVAS methodology and interesting value proposals were generated for the target market.